МОЖЛИВОСТІ СКОРОЧЕННЯ І ЗАМІЩЕННЯ СПОЖИВАННЯ ПРИРОДНОГО ГАЗУ В ЦЕНТРАЛІЗОВАНОМУ ТЕПЛОПОСТАЧАННІ УКРАЇНИ - Geletukha, G.G.; Zheliezna, T.A.; Drahniev, S.V. (Institute of Engineering Thermophysics of NAS of Ukraine, 2022)
The aim of the work is to identify and analyze the necessary steps for Ukraine to reject Russian natural gas. Russia's war against Ukraine has challenged our country, the EU and the world to an urgent introduction of embargo on the purchase of oil, gas and coal from the aggressor country. Unfortunately, Ukraine has to buy about 40% of its energy abroad, including from Russia, the required import of natural gas in recent years being 8… 10 billion m3/year. With the projected development plans and implementation of the proposed measures, by 2030, Ukraine will be able to completely reduce/replace the imported natural gas in the amount of up to 10 billion m3/year and become independent of it. By 2050, the volume of the reduction/replacement of natural gas may reach almost 26 billion m3/year. Substitution of natural gas with biomass and solid biofuels in heat production is one of the most cost-effective ways, especially given the current and projected high prices of natural gas in the EU, where Ukraine is currently purchasing it. In addition, Ukraine can potentially produce up to 10 billion m3 of biomethane/year, mainly from agricultural waste and residues such as manure, cereal straw, corn stalks, sunflower stalks, sugar beet pulp, molasses, corn silage, as well as municipal waste and other types of biomass. By 2050, the total production of biogas/biomethane in the country may reach 6 billion m3/year, some of which can be exported. We believe that Ukraine as soon as possible needs to develop an effective and ambitious state program to reduce and replace the consumption of imported gas, which should be the basis for the recovery of Ukraine's energy sector.